A teacher for all generations : essays in honor of James C. Vanderkam - VanderKam, James C.; Mason, Eric Farrel. (Supplements to the Journal for the Study of Judaism, 2012)
This collection of essays honors James C. VanderKam on the occasion of his sixty-fifth birthday and twentieth year on the faculty of the University of Notre Dame. An international group of scholars-including peers specializing in Second Temple Judaism and Biblical Studies, colleagues past and present, and former students-offers essays that interact in various ways with ideas and themes important in VanderKam's own work. The collection is divided into five sections spanning two volumes. The first volume includes essays on the Hebrew Bible and ancient Near East along with studies on Qumran and the Dead Sea Scrolls. Essays in the second volume address topics in early Judaism, Enoch traditions and Jubilees , and the New Testament and early Christianity.